The Effect Of Administration Of Salam Leaf Extract (Eugenia Polyantha) On Hdl And Ldl Colesterol Levels In Prolanis Patients At Iman Clinic - Tarigan, Alwi Friendly; Rahman, Shahrul (ANATOMICA MEDICAL JOURNAL | AMJ, 2023)
Lipids are a component of micro-substance molecules in the body that function as structural components in cell membranes and can also be used as a source of energy for the body. Lipid levels in the blood can be measured by examining the total cholesterol, triglycerides, HDL, LDL and VLDL. This study analyzed the effect of bay leaf extract on HDL and LDL cholesterol levels in Prolanis patients at Iman clinic. Its an experimental pretest-posttest study using 38 elderly (45 years) divided into the experimental and control group. The results showed that the average effect on HDL cholesterol levels was 40.37 mg/dL pretest and 40.11 mg/dL posttest, LDL cholesterol levels found an average value of 119.58 mg/dL pretest and posttest 130.63 mg/dL in the experimental group, whereas in the control group it was found that the effect of giving the extract on HDL and LDL cholesterol levels was not significant. The significance value based on the Wilcoxon statistical test was 0.461 for HDL cholesterol levels and 0.953 for LDL cholesterol levels. Conclusion: There is no effect of bay leaf extract (Eugenia Polyantha) on HDL and LDL cholesterol levels in prolanis patients at the Iman clinic.Keywords: Lipid, Bay Leaf, HDL and LDL Cholesterol Levels